THE STRATEGY OF THE NATIONAL AMIL ZAKAT AGENCY (BAZNAS) NORTH SUMATRA IN INCREASING MUZAKKI AWARENESS TO PAY PROFESSIONAL ZAKAT - Purba, Gilang Maulana; Abdurrahman (Pena Cendekia Insani, 2025)
Professional zakat is one type of zakat with significant potential to support the economic development of the Muslim community. However, the level of awareness among muzakki (zakat payers) in North Sumatra to fulfill professional zakat obligations remains relatively low. This study aims to analyze the strategies implemented by the National Zakat Agency (BAZNAS) of North Sumatra Province in increasing muzakki awareness in paying professional zakat. A descriptive qualitative method was employed, using in-depth interviews, observation, and documentation as data collection techniques. The results reveal that BAZNAS North Sumatra applies strategies such as direct socialization to government agencies and communities, digital campaigns via social media, and collaboration with religious leaders and public figures. The challenges faced include low zakat literacy and limited public participation. This study recommends enhancing educational innovation and utilizing technology to expand the reach of zakat campaigns.